Economic Benefits of Sustainable Construction Avantages économiques de la construction durable - Azazga, Imene (Finance and Business Economies Review, 2019)
This article discusses the economic benefits of sustained construction; it demonstrates the economic value of green construction projects. As a step to depict the contribution of ecological construction to the development and to the growth of economies, this study has shown the principles of sustained construction and their direct and indirect economic impacts. It concludes that sustained construction projects affect economic growth through two main advantages; these are: less energy consumption and expenditures, and economic efficiency.